2005
DOI: 10.1038/sj.ijo.0803112
|View full text |Cite
|
Sign up to set email alerts
|

Serum TSH is positively associated with BMI

Abstract: Objective: To investigate whether there is an association between serum thyroid-stimulating hormone (TSH) within the normal range and body mass index (BMI). Design and subjects: The study was performed in 6164 subjects (2813 males) who attended the fifth Tromsø study in 2001, and in 1867 subjects (873 males) that attended both the fourth Tromsø study in 1994/1995 as well as the fifth Tromsø study. Measurements: Height, weight, and serum TSH were measured in all subjects, and smoking status was recorded. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
196
16
7

Year Published

2008
2008
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(238 citation statements)
references
References 32 publications
(27 reference statements)
19
196
16
7
Order By: Relevance
“…In a large population study conducted in euthyroid patients from Denmark, 3 the body mass index (BMI) was found to be positively associated with serum TSH and inversely related to free tetraiodotyronine (FT 4 ). This finding has been confirmed in other studies, [4][5][6] but not in all. 7 However, in the latter report, study participants were referrals to a thyroid clinic.…”
Section: Introductionsupporting
confidence: 82%
“…In a large population study conducted in euthyroid patients from Denmark, 3 the body mass index (BMI) was found to be positively associated with serum TSH and inversely related to free tetraiodotyronine (FT 4 ). This finding has been confirmed in other studies, [4][5][6] but not in all. 7 However, in the latter report, study participants were referrals to a thyroid clinic.…”
Section: Introductionsupporting
confidence: 82%
“…There are several lines of evidence that suggest serum cystatin C may have extra-renal sources, particularly in pathways that may associate with body weight. Serum cystatin C has been shown to be associated with thyroid function, corticosteroid administration, and C reactive protein, conditions that are associated with alterations in body weight [24][25][26] . Thus, there may be additional potential mechanisms for the association between BMI and serum cystatin C, observed in the current study, above and beyond kidney function.…”
Section: Discussionmentioning
confidence: 99%
“…The potential impact of minor changes in thyroid function on body weight and other anthropometric measures, especially in euthyroid subjects (4)(5)(6), has been investigated. Thus, the definition of the upper limit of normal serum TSH range has been under intense debate in the literature (7,8).…”
Section: Introductionmentioning
confidence: 99%